Strategi Peningkatan Efisiensi Waktu Bongkar Muat Antara Dermaga dan Container Yard di PT. Terminal Teluk Lamong - Nabila Aisya Savitri; Elly Kusumawati; Vigih Hery Kristanto (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine the condition of existing activities in loading and unloading at the Teluk Lamong Terminal Port. Also, to find out how the strategy is to increase the effiency of loading and unloading time between the pier and container yard at Teluk Lamong Port based on a comparison of performance before and after the implementation solution. The background of this study based on the importance of operational efficiency of the Port in supporting smooth logistic and increasing the competitiveness of the marine transportation sector. The method used in this study is mix methods, which is a combination of qualitative and quantitative approaches. Data collection was carried out through direct observation, interviews with related parties, field documentation, and statistical analysis using normality, homogeneity, and t-test tests. The findings show that the additional of equipment can significantly reduce loading and unloading process time and increase work effectiveness. Thus, the use of this tool contributes to improving operational performance at Teluk Lamong Terminal and supports faster and more efficient logistic services.